Golden years happiness: analyzing the nostalgic aspect of leisure - Onal, Levent; Bedir, Fatih; Turan, Murat; Mavibas, Muhammet; Savaş, Buğra Çağatay; Yasarturk, Fatih (Frontiers in Psychology, 2024)
Retirees face numerous challenges, particularly in countries with lower socio-economic conditions. Perceived social isolation and happiness levels are seen as significant factors that significantly affect the quality of life in old age. Perceived social happiness levels can disrupt the quality of life in old age and contribute to mental disorders. Recent studies on leisure have suggested a direct impact of individuals’ leisure attitudes on happiness. In this context, leisure nostalgia stands out in the relationship between leisure attitude and happiness levels among retirees. In this study, structural equation modeling (SEM) was employed to examine the relationship between leisure attitude, leisure nostalgia, and happiness levels in a sample of 210 retirees. The findings revealed that leisure nostalgia fully mediated the relationship between leisure attitude and happiness. It was concluded that previous experiences significantly shape retirement, and leisure attitude offers valuable opportunities for enhancing happiness through effective leisure utilization.